Embosphere Size Selection and Dilution Rate in Preoperative Tumor Embolization of the External Carotid Artery System Using a Small-diameter Catheter - Takao HASHIMOTO; Yusuke ARAI; Hirofumi OKADA; Muneaki KIKUNO; Hiroki SAKAMOTO; Kyosuke MATSUNAGA; Michihiro KOHNO (Neurologia Medico-Chirurgica)
The widespread adoption of preoperative embolization in highly vascularized brain tumors often involves the frequent use of Embosphere (Merit Medical Systems, South Jordan, Utah, USA). Nevertheless, inconsistency in size selection and dilution rates across different institutions requires comprehensive examination. This study explored the appropriate size and dilution rate of Embosphere microspheres. To assess catheter occlusion and Embosphere breakage, various dilutions (4-, 10-, 20-, 30-, and 60-fold) of Embosphere 300-500 and 500-700 μm were injected into the catheter in vitro. Results indicated that 20-fold or higher dilutions of Embosphere 300-500 μm and 30-fold or higher dilutions of Embosphere 500-700 μm showed no occlusion of the Excelsior SL-10 microcatheter (Stryker, Fremont, CA, USA) or Embosphere breakage. For embolization, to reduce the risk of Excelsior SL-10 occlusion further, a 30-fold dilution of Embosphere 300-500 μm and a 60-fold dilution of Embosphere 500-700 μm were employed. For 195 blood vessels in 107 patients (84 with meningioma and 23 with schwannoma), embolization was carried out using a 30-fold dilution of Embosphere 300-500 μm when the provocative test was negative and a 60-fold dilution of Embosphere 500-700 μm when the test was positive or when there was a risk of migration into neurotrophic vessels. Contrast-enhanced magnetic resonance imaging after embolization revealed a reduced enhancement effect in 69.1% of cases. Embolization using a 30-fold dilution of Embosphere 300-500 μm and a 60-fold dilution of Embosphere 500-700 μm with an Excelsior SL-10 catheter is safe and satisfactory, which minimizes microcatheter occlusion.